O rádio além das ondas hertzianas : emissoras de Porto Alegre - Brito, Wanderlei de (2015)
This research focuses on examining how the traditional radio stations are exploring the new broadcasting and sound storage data platforms. It is also noticed how the radio, before restricted to a granted channel amplitude modulation (AM) or frequency modulation (FM) this one limited to geographical area, has now technological appliances which enable an unlimited coverage and the offers of multi-channels through internet, satellites, integrated cables or non-integrated cables to the broadcasting systems. It is yet noticed, how these new digital platforms are being used in the dissemination of broadcast radio contents, before restricted of radio waves and now digitalized, taking new attributions, being offered in a real time alternative way or on-demand. In this sense, 30 radio stations on radio waves broadcasting from Porto Alegre and programming focusing this market are analyzed to ascertain the main changes, consequences and impacts caused by the use of new technologies on the production and usage of sound and broadcasting contents related to digitalization and internet. It is observed that the free internet flow boosts and competes with the traditional radio broadcast content.